In vitro anthelmintic activity of Heliotropium indicum, Senna fistula and Spigelia anthelmia used as worm expeller in South West Nigeria - Sobiyi, Oluwakemi K.; Ashafa, A. O. Tom (Bangladesh Journal of Pharmacology, 2015)
The anthelmintic potential of Heliotropium indicum, Senna fistula and Spigelia anthelmia were investigated using nematodes larvae from sheep and adult earthworms in order to justify the folkloric claim of the plants as worm expeller in south west of Nigeria. The acetone, ethanol, hydro-alcohol and distilled water extracts showed dose-dependent anthelmintic activities at the different concentrations (0.25, 0.50, 1.0 mg/mL) when tested against nematodes larvae. The order of anthelmintic effect for the plants was H. indicum> S. fistula> S. anthelmia. Acetone and ethanol extracts of the three plants showed the most effective activity (100% mortality) against adult earth worm (Pheretima posthuma) after 30 min of exposure The reference standard drug (Vermox®) showed less effectiveness compared to the medicinal plants used in the study. Overall, the study indicates that Heliotropium indicum, Senna fistula and Spigelia anthelmia are potential anthelmintic herbal drugs, which in turn validates the use of the three species as worm expellers by the Yorubas tribe of South West Nigeria.